PENGARUH TINGKAT PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) TERHADAP PROFITABILITAS DAN DAMPAKNYA TERHADAP ZAKAT PERUSAHAAN - Titiek Herwanti; Muhammad Irwan; Nur Fitriyah (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
The objective of this study is to examine the influence of the level of Islamic Social Reporting (ISR) disclosure to the profitability and its impact on the amount of zakat must be paid by the Islamic banking companies in Indonesia. This study uses documentary studies with associative research’s type. Samples using purposive sampling method and was elected eight Islamic Banks in Indonesia. The observation period from 2009 until 2013 with a lag time t+1. Data were analyzed by using Partial Least Square (PLS) with Smart PLS program. The collection of data derived from secondary data, financial statements and annual reports published by Bank Indonesia website and the website of each Islamic Banks. The results show that the Islamic Social Reporting level of disclosure has a significant and positive influence to the profitability of the Islamic banking company who reflected by return on assets ratio (ROA) and return on equity ratio (ROE). The profitability of the Islamic banking company has a significant and positive influence on the number of zakat companies to be paid by the Islamic Banks in Indonesia